2019
DOI: 10.1080/01924036.2019.1615520
|View full text |Cite
|
Sign up to set email alerts
|

Environmental crime prosecutions in Ireland, 2004–2014

Abstract: Despite increased interest in environmental crime and green criminology, few studies address the use of criminal penalties in response to environmental crimes. A handful of published examples employ data from the United States or the Flanders court system, and little is known about how other nations punish environmental violations. Addressing this issue, the current study examined the use of criminal environmental penalties in Ireland from 2004 to 2014. Few criminal environmental cases (N = 147) and few enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…For example, Lynch et al pointed out to the low number of criminal penalties for environmental crimes in Ireland-for the examined period of 11 years, it can be concluded that there were about 14 environmental punishments per year, which is disproportionate to other offences. At the same time, the majority of offenders in question were corporations [16].…”
Section: Environmental Criminal Offences and The Rights Of Victims And Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lynch et al pointed out to the low number of criminal penalties for environmental crimes in Ireland-for the examined period of 11 years, it can be concluded that there were about 14 environmental punishments per year, which is disproportionate to other offences. At the same time, the majority of offenders in question were corporations [16].…”
Section: Environmental Criminal Offences and The Rights Of Victims And Offendersmentioning
confidence: 99%
“…It should be established at an early stage that despite the large number of environmental violations, there is only a low number of criminal environmental cases [5,16]. What is perhaps even more alarming, though, is that when there is an environmental criminal procedure, the public-assuming the position of an injured party or a victim of an environmental harm with implications for a larger part of the society-seems to be virtually deprived of the possibility to participate in it [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to prevention, it is very important to take a reactive approach to criminalize acts of environmental degradation and pollution; By identifying and expanding the competence of those in charge, from public and governmental to private and non-governmental, the protection of privacy will become a better and easier process. Therefore, the interaction of non-governmental organizations with the government and the competence of these organizations in environmental criminal cases has an important role in protecting the environment in the control and enforcement phase [11][12][13][14][15][16][17].…”
Section: Of 14mentioning
confidence: 99%
“…Sometimes the actions of these organizations are such that they can be considered in the formation of minimum criteria, for example, companies producing products and food products or even health and pharmaceuticals and clothing and services to maintain their credibility in the market and Also, their convenience from the buyer point to the logo of the licensing of these institutions as a proof of the high quality of their products on their goods. Despite the many efforts of non-governmental organizations in Iran, these organizations have not yet been able to find their true place properly and act in an integrated manner in mobilizing public opinion to protect the environment and prevent environmental crimes [15,16].…”
Section: Public Opinion Pollsmentioning
confidence: 99%
“…White, 2011). This results in a general sense of impunity (Pereira, 2015), insofar as both the perception of the risk of being caught and the probability of a criminal prosecution are extremely low for environmental crimes (Lynch et al,2016, 2019; Morganti et al, 2020; Sahramäki et al, 2017). In addition, the financial losses stemming from potential punishment are often negligible for waste traffickers (Bisschop, 2012).…”
Section: Problem Formulationmentioning
confidence: 99%